Analisis Faktor yang Mempengaruhi Minat Belanja Online Pada Mahasiswa di Pulau Bengkalis - Tiara Rahmadani; Nilam Sahana; Suci Hikmatul Jannah; Alya Yunita (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to determine the factors that influence online shopping interest for students on Bengkalis Island. The method used in this study is quantitative-qualitative method. The sample of this study was students at two universities on Bengkalis Island, namely the Bengkalis State Polytechnic Campus and STAIN Bengkalis. The focus of the research is students from two Universities who have made payments online within the past six months. The sampling method used in this study is non probability Â Â sampling. Non probability sampling is a sampling technique that does not use election rules. The results of this study indicate that the variables, Atmosphere, Product, Price, Promotion, Trust, Service, and Orientation partially and simultaneously influence and significantly influence the interest of online shopping.